2003
DOI: 10.1074/jbc.m304781200
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Acetylcholinesterase and the Organophosphate-inhibited Form Using Antibodies and the Correlation of Antibody Recognition with Reactivation Mechanism and Rate

Abstract: Two types of polyclonal antibodies were generated from (a) a decapeptide sequence that includes the active site serine of acetylcholinesterase (anti-AChE 10S ) and (b) the identical decapeptide sequence phosphorylated at the active site serine of acetylcholinesterase (antiAChE 10SP ). The anti-AChE 10S antiserum was found to specifically recognize native, control, and vehicletreated recombinant mouse AChE (rMoAChE) but did not recognize rMoAChE that was phosphorylated by the four organophosphate (OP) compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
2
26
1
Order By: Relevance
“…Previously, a report showed that antibodies could distinguish phosphorylated AChE and inhibited AChE using this strategy (George et al, 2003), but despite their utility, these polyclonal anti-phosphorylated AChE antibodies did not have the ability to distinguish different OP adducts. The results of that report did suggest that it was possible to raise antibodies to individually recognize specific modifications of the dianionic phosphorus of OP-adducted proteins (George et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, a report showed that antibodies could distinguish phosphorylated AChE and inhibited AChE using this strategy (George et al, 2003), but despite their utility, these polyclonal anti-phosphorylated AChE antibodies did not have the ability to distinguish different OP adducts. The results of that report did suggest that it was possible to raise antibodies to individually recognize specific modifications of the dianionic phosphorus of OP-adducted proteins (George et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the approach to detect protein-OP adducts has relied on MS (Thompson et al, 2010), although one report showed that antibodies could be raised against phosphorylated AChE (George et al, 2003). However, in that report, the antibodies reported to recognize the inhibited form of AChE did not distinguish OP-AChE adducts arising from different OPs (George et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). A number of studies have been undertaken to understand the chemical nature of the OP-AChE modification [3,[8][9][10][11][12][13][14]. Importantly, OP-AChE conjugates differ in the phosphoester ligands, which defines a unique molecular weight identifier for analysis and potentially a method for discriminating between OP-AChE conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MS methods developed for rMoAChE will be applicable to other mammalian AChEs, and other select esterases (e.g., butyrylcholinesterase) bearing homologous active-site sequences. To further aid the analysis, the active-site serine inclusive peptides TLFGESAGAA (AChE 10S ) [14] and GESAGAASVGMHIL (AChE 14S ; equivalent to the chymotryptic fragment, Fig. 1), were synthesized and used to develop methods for detection of the active-site peptide from rMoAChE.…”
Section: Introductionmentioning
confidence: 99%